(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Spectrum of fungal pathogens in nails are determined. 47 samples of nails from patients are examined. Predominant etiologic agent of feet onychomycosis was Trichophyton sp. (T. rubrum – 65%) and species of the genus Candida (21%) – C. albicans, C. parapsilosis, C. tropicalis. The theory is used, confirmed the effectiveness of the calculation of the clinical index recommended by A.Yu. Sergeev and Yu.V. Sergeev as the most objective means to treat onychomycosis.